"One body and two wings" novel nanozyme combined with photothermal therapy for Combat Drug-Resistant Bacteria. (September 2022) - Huang, Dongwei; Hu, Xianyue; Wang, Chenxia; Zhu, Dan; Tang, Min
Bacterial resistance caused by antibiotic therapy is a serious problem. Therefore, there is an urgent need to find alternative methods to overcome bacterial resistance. Herein, we synthesized a new type of iridium oxide (IrOx) as an alternative to antibiotics. Iridium oxide not only has good catalytic properties, but also has photothermal properties, and then realizes the "one body and two wings" strategy to enhance the antibacterial effect. Research results show that near-infrared light can enhance the peroxidase catalytic activity of IrOx and generate highly toxic hydroxyl radicals (·OH) by catalyzing hydrogen peroxide (H2 O2 ). Hydroxyl radicals have a high redox potential, which can overcome the drug resistance of gram-positive and negative bacteria. Importantly, IrOx has no obvious cellular and in vivo toxicity. Accordingly, the novel photothermal nanozyme is expected to be applied to bacterial infectious diseases, such as wound healing, sepsis, and implant-related infections.